Взаємодія адвокатури з органами державної влади та іншими суб’єктами владних повноважень - Бандурка, С. С.; Bandurka, S. S. (Право.ua. - 2023. - № 4, ч. 2. - С. 71-80, 2023)
Розглянуто взаємодію адвокатури і державних органів влади з урахуванням особливостей діяльності в умовах воєнного стану при повній пріоритетності принципу захисту прав і свобод людини як основного завдання держави.

The legal profession, throughout its entire formation and development, constantly interacts with state authorities and other legal entities endowed by the state with governing powers. The legal profession does not operate in isolation; its activities and provision of legal assistance are integral components of the overall activities of the state authorities, local self-government bodies, and citizens' associations authorized to provide services to the population in realizing their legal rights and freedoms, the interests of legal entities, the state, and society. In this regard, the article examines the role and place of the legal profession in the system of state authorities and other subjects with governing powers. It emphasizes that according to Article 59 of the Constitution of Ukraine, everyone has the right to professional legal assistance, and for the provision of professional legal assistance in Ukraine, there is the legal profession, which is integrated into the judiciary system. The competence and powers of state authorities in Ukraine, local self-government bodies, judicial authorities, and citizens' associations are characterized. It is argued that the constitutionality of the independence principle of the legal profession is one of the defining principles of the organization and activities of the legal profession. It is shown that civil society cannot exist without a developed and independent institution of the legal profession. In modern conditions of the state of war caused by Russian aggression against Ukraine, the protection of human rights and freedoms has acquired not only a national character but also become an international problem, and the role and significance of the legal profession have immensely increased. It is noted that human rights, subject to protection, are not an achievement of a separate legal system; they are developed and defined by the global community, and their protection is envisaged not only by national legislation but also by a series of international legal acts ratified by Ukraine. Speaking about the interaction of the legal profession with the system of state authorities and other subjects with governing powers, the author believes that it is necessary to consider that the system, in this case, represents the totality of all state authorities, institutions, organizations that constitute a coherent mechanism of state governance, interconnected by the necessary and sufficient structure for achieving the goals of interaction and relations between its elements. Elements of the system include military administrations, district and state administrations, territorial units of central executive bodies, ministries and their structural subdivisions, departments, committees, administrations, associations, and other state bodies and local self-government bodies with their executive structures. The legal profession of Ukraine interacts both with the entire system of state authorities and local self-government and with each of its individual elements. Each element of the system of state authorities and local self-government is its subsystem and has its powers and competence established by regulatory legal acts. The legal profession of Ukraine is a subsystem in the system of Ukraine'sjud iciary and operates based on the Constitution of Ukraine, the Law of Ukraine «On Advocacy and Legal Practice,» other laws of Ukraine, including the Criminal Procedure Code of Ukraine, the Criminal Code of Ukraine, the Civil Code of Ukraine, the Code of Administrative Judicial Procedure of Ukraine, and relevant international legal acts.

Рассмотрено взаимодействие адвокатуры и государственных органов власти с учетом особенностей деятельности в условиях военного положения при полной приоритетности принципа защиты прав и свобод человека как основной задачи государства.
Keywords: адвокатура; advocacy; державні органи; government agencies; государственные органы; органи місцевого самоврядування; local governments; органы местного самоуправления; взаємодія; interaction; взаимодействие; правова допомога; legal aid; правовая помощь; захист прав і свобод людини; protection of human rights and freedoms; защита прав и свобод человека